NAD+ modulation of intestinal macrophages renders anti-inflammatory functionality and ameliorates gut inflammation - Kim, Young In; Ko, Inseok; Yi, Eun Je; Kim, Jusik; Hong, Yong Rae; Lee, Wheeseong; Chang, Sun Young (Biomedicine and Pharmacotherapy, 2025)
Macrophages can maintain gut immune homeostasis by driving clearance of infection, but also can prevent chronic inflammation and induce tissue repair. Reduced nicotinamide adenine dinucleotide (NAD+) levels in macrophages have been reported to be associated with the onset of severe colitis. Given that dysregulation of gut macrophages plays a significant role in inflammatory bowel disease (IBD), they represent a potential target for novel therapies. Here we show an IBD therapeutic candidate LMT503, a substrate that modulates NADH quinone oxidoreductase (NQO1), which induces anti-inflammatory macrophage polarization by NAD+ enhancement. To determine the anti-inflammatory effect of LMT503, a dextran sulfate sodium (DSS)-induced colitis mouse model was used in this study. Treatment of bone marrow-derived macrophages (BMDMs) with LMT503 increased IL-10 and Arg1 levels but decreased levels of TNF-α, iNOS, and IL-6. LMT503 also increased levels of SIRT1, SIRT3, and SIRT6, suggesting that macrophages were driven to an anti-inflammatory character. In a murine DSS-induced colitis model, oral treatment with LMT503 ameliorated colonic inflammation and decreased infiltrating monocytes and neutrophils. Although NAD+ enhancement did not alter CX3CR1intCD206- or CX3CR1hiCD206+ colon macrophage population, it decreased levels of TNF-α and iNOS and increased IL-10 level, with colonic macrophages showing an anti-inflammatory character shift. Depletion of CX3CR1 expressing gut resident macrophages abrogated the immune regulatory effect of LMT503 in the colon. These data suggest that LMT503 is a therapeutic candidate that can target macrophages to drive polarization with an immunosuppressive character and ameliorate IBD.
Keywords: Animals; Anti-Inflammatory Agents; Colitis; Colon; Cytokines; Dextran Sulfate; Disease Models, Animal; Inflammation; Inflammatory Bowel Diseases; Intestines; Macrophages; Male; Mice; Mice, Inbred C57BL; NAD; NAD(P)H Dehydrogenase (Quinone); Colon; Gut macrophage; Inflammatory bowel disease; Macrophage polarization; NAD+ modulation